Comparative transcriptomic and proteomic analyses provide insights into the key genes involved in high-altitude adaptation in the Tibetan pig - Bo Zhang (Nature Portfolio, 2017)
Abstract Tibetan pigs that inhabit the Tibetan Plateau exhibit striking phenotypic and physiological differences from lowland pigs, and have adapted well to extreme conditions. However, the mechanisms involved in regulating gene expression at high altitude in these animals are not fully understood. In this study, we obtained transcriptomic and proteomic data from the heart tissues of Tibetan and Yorkshire pigs raised in the highlands (TH and YH) and lowlands (TL and YL) via RNA-seq and iTRAQ (isobaric tags for relative and absolute quantitation) analyses, respectively. Comparative analyses of TH vs. YH, TH vs.TL, TL vs. YL, and YH vs. YL yielded 299, 169, 242, and 368 differentially expressed genes (DEGs), and 473, 297, 394, and 297 differentially expressed proteins (DEPs), respectively. By functional annotation of these DEGs and DEPs, genes that were enriched in the HIF-1 signaling pathway (NPPA, ERK2, ENO3, and EGLN3), VEGF signaling pathway (ERK2, A2M, FGF1, CTGF, and DPP4), and hypoxia-related processes (CRYAB, EGLN3, TGFB2, DPP4, and ACE) were identified as important candidate genes for high-altitude adaptation in the Tibetan pig. This study enhances our understanding of the molecular mechanisms involved in hypoxic adaptation in pigs, and furthers our understanding of human hypoxic diseases.